Analytical comparison of two distinct receiver tubes of a parabolic trough solar collector system for thermal application. (2020) - Thappa, Sahil; Chauhan, Aditya; Anand, Yatheshth; Anand, Sanjeev
Abstract: Parabolic trough collectors (PTC) are being used to harvest solar energy for electricity generation and other thermal applications for the last few decades. Many investigations and necessary modifications have been done in the field of PTC systems till now. But still, the design of the PTC system is being studied to have an increased system performance. This is one such investigation in which the objective is to demonstrate the effect of receiver tube size for a particular parabolic trough reflector surface. This study gives a comparison between two distinct receiver tubes for the same parabolic reflector and also reports how the size of a receiver tube is responsible for variation in output parameters of a system. This paper is an analytical comparison of receiver tube diameter of an existing system, considering it as a reference to another receiver tube with different diameter found out empirically. The presented results report the effect of variation in diameter of the receiver tube on loss coefficient, energy gain and system efficiency for a temperature ranging from 400 K to 600 K.